How Much Does It Cost to Be Middle Class in The Bahamas? - Archer, Lesvie Nicole (International Journal of Bahamian Studies, 2024)
This study estimates cost-of-living expenses for middle-class families in The Bahamas. It is an extension of the 2020 Bahamas Living Wages Survey (2021b) that provided cost-of-living estimates for lower-income families using the Anker and Anker methodology that combines primary data collection through surveys with analysis of secondary data using statistical reports and government documents. The study reveals that, as of March 2024, a middle-class family of four requires an income of $10,200 monthly if living in New Providence and $10,100 monthly if living in Grand Bahama. These estimates are higher than the updated estimates generated for lower-income families by 104% in New Providence and by 53% in Grand Bahama. This brief report may be a starting point for informing policies related to wages, living costs and living standards in The Bahamas.